2004
DOI: 10.1007/s10350-004-0524-0
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Electrophysiologic Anal Tests in Predicting the Outcome of Sacral Nerve Modulation for Fecal Incontinence

Abstract: Simple anal sphincter electromyography can predict the outcome of the peripheral nerve evaluation with good positive predictive value and specificity in patients with fecal incontinence. Other, more expensive, electrophysiologic anal tests do not add further prognostic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…Our results do not agree with a previous report, which showed that a normal anal sphincter electromyography had a good positive predictive value for the outcome of the stimulation test. 17 Results were different after permanent implantation. According to our data, patients with a prolonged sacral reflex showed a better response to permanent stimulation than those with a normal reflex latency.…”
Section: Discussionmentioning
confidence: 91%
“…Our results do not agree with a previous report, which showed that a normal anal sphincter electromyography had a good positive predictive value for the outcome of the stimulation test. 17 Results were different after permanent implantation. According to our data, patients with a prolonged sacral reflex showed a better response to permanent stimulation than those with a normal reflex latency.…”
Section: Discussionmentioning
confidence: 91%
“…in any case, the clinical value of grading atrophy has not yet been established. 32,33 Our study had several limitations. This result is consistent with previous observations by Terra et al 2 and Voyvodic et al 26 The value of measuring PNTML in defining pudendal neuropathy remains controversial, [27][28][29] and no correlation has been found between prolonged PNT-ML and anal squeeze pressures.…”
Section: Discussionmentioning
confidence: 94%
“…Direct motor contraction of the external sphincter may also occur at higher amplitudes. Normal EAS electromyography has previously been shown to be a significant predictive factor for successful outcome in the treatment of FI by SNS [20]. It has also been suggested that the amplitude required to elicit a reflex response is dependent on the proximity of the electrode to the nerve [6].…”
Section: Discussionmentioning
confidence: 99%